Structure of the LiPs and $e^+$Be Systems (Journal of Atomic and Molecular Sciences, 2010)
Close to converged energies and wave functions for the positron binding systems, LiPs and $e^+$Be are computed using the stochastic variational method. Binding energies and annihilation rates from both $ab$-$initio$ and fixed core calculations are determined and found to be in agreement. The $ab$-$initio$ binding energy of $e^+$Be was 0.00316 Hartree while that for LiPs was 0.01237 Hartree.
Keywords: positron; positronium; stochastic variation method; atomic structure; positronic atom.